Approval Of Sirri Marriage From The Perspective Of Islamic Law And State Law And Its Influence On The Position Of Wife, Children, And Property - Chafidzul Hakim Noer; Dahlan Thamrin; Budi Parmono (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
Unregistered marriage (nikah sirri) is a complex legal phenomenon in Indonesia, as it is considered valid under Islamic law but not recognized by state law due to a lack of registration. This research aims to analyze the impact of unregistered marriages on the status of wives, children, and property from the perspectives of Islamic law and Indonesian positive law. The method used is normative juridical research with conceptual, legislative, and fiqh approaches. Primary data sources include Law Number 1 of 1974 on Marriage, the Compilation of Islamic Law, and the Quran and Hadith, while secondary data are derived from relevant academic literature. The findings show that according to Islamic law, an unregistered marriage that fulfills the pillars and requirements is valid, thus wives, children, and property have the same status as registered marriages. However, under Indonesian positive law, unregistered marriages have no legal force because they are not registered at the Office of Religious Affairs or Civil Registry Office, resulting in wives lacking legal protection of their rights, children only having civil relations with their mothers, and joint property cannot be submitted to court without marriage confirmation (itsbat nikah). This research recommends the need for socialization on the importance of marriage registration and stricter law enforcement to protect the rights of women and children.